L'approche hydrogéomorphologique : pratiques, valorisations et développement d'une méthode de cartographie des zones inondables - Montané, Antonin (Université Paul Valéry - Montpellier III, 2014)
La connaissance de l’aléa inondation est un enjeu croissant pour la gestion du risque inondation. En France, afin de répondre à la demande des pouvoirs publics de cartographier les zones inondables, la cartographie hydrogéomorphologique émerge. Cette approche naturaliste, développée durant les années 1980, se propagea dans une large partie du Sud de la France. Aujourd’hui, la cartographie hydrogéomorphologique est une méthode reconnue pour sa fiabilité, mais elle stagne en termes d’applications et de développement dans de nouveaux territoires. Afin d’améliorer la connaissance de la prise en compte de la cartographie hydrogéomorphologique dans un cadre règlementaire, une analyse de 282 PPRI a été menée. Cette analyse a permis de dégager les modalités de prise en compte de la cartographie hydrogéomorphologique, mais également d’émettre des hypothèses sur les raisons de leur développement. La réalisation de MNZI (Modèle Numériques de Zones Inondables) sur des cours d’eau français et canadiens, a permis de mettre en avant l’adaptabilité de la cartographie hydrogéomorphologique à des contextes physiques différents, mais aussi d’apporter une réponse à la demande de prise en compte de cartographie de crue extrême de la Directive Inondation. L’évolution cartographique proposée dans ce travail comprend une réflexion autour de la légende des AZI, mais aussi sur le concept de cartographie positive. A travers les aspects cartographiques, règlementaires et géomorphologiques abordés, nous finissons par proposer un modèle de développement de la cartographie hydrogéomorphologique.
Keywords: Ouvrage_Collectif_Numéro1

Socioeconomic development and the impact of natural disasters: some empirical evidences from China - Zhou, Yang; Li, Ning; Wu, Wenxiang; Liu, Haolong; Wang, Li; Liu, Guangxu; Wu, Jidong (Natural Hazards, 2014)
Significant advancements have been made in examining the relationship between economic development and disaster losses at the global and national scales, but very little research has been done at the sub-national level, especially in China. Based on socioeconomic and disaster impact data from 31 provinces (municipalities, and autonomous regions) in China from 1990 to 2010, ordinary least squares regression was used to determine the relationship between socioeconomic development and effects of natural disasters. Results showed that economic development played a distinct role in mitigating disaster damages in the whole China and its eastern, central and western regions. There existed a U-shaped relationship between economic growth and disaster losses in the whole China and its eastern region, and an inverted-U nonlinearity linkage in its central and western areas. These findings further confirmed the existence of a nonlinear relationship between economic development and disaster losses. Economic growth had played a more important role in mitigating disaster losses in the central region of China than that in the western one. Further investigations demonstrated that as economic develops, there were fewer deaths caused by natural hazards in whole China and all its three regions. The combination of the lower level of education, higher unemployment rate and greater gross dependence ratio has contributed to the increase in death toll caused by natural disasters, but this trend could be partly offset by wealth growth.

Social and spatial inequities in exposure to flood risk in Miami, Florida - Chakraborty, Jayajit; Collins, Timothy W.; Montgomery, Marilyn; Grineski, Sara E. (Natural Hazards Review, 2014)
AbstractAlthough environmental justice (EJ) research in the United States has traditionally focused on technological hazards such as air pollution or hazardous waste, the adverse and unequal impacts of Hurricane Katrina have prompted researchers to examine the EJ implications of natural events such as hurricanes and floods. This paper contributes to this emerging literature on EJ and social vulnerability to natural hazards by analyzing racial/ethnic and socioeconomic inequities in the distribution of flood risk exposure in the Miami Metropolitan Statistical Area (MSA), Florida—one of the most hurricane-prone areas in the world and one of the most ethnically and socioeconomically diverse MSAs in the United States. Although previous studies have relied exclusively on the 100-year floodplain to assess the spatial extent of flood exposure, this study makes a systematic distinction between different types of flood zones on the basis of both the probability (100-year versus 500-year versus low/no risk) of flood...

On the relation between weather-related disaster impacts, vulnerability and climate change - Visser, Hans; Petersen, Arthur C.; Ligtvoet, Willem (Climatic Change, 2014)
Disasters such as floods, storms, heatwaves and droughts can have enormous implications for health, the environment and economic development. In this article, we address the question of how climate change might have influenced the impact of weather-related disasters. This relation is not straightforward, since disaster burden is not influenced by weather and climate events alone—other drivers are growth in population and wealth, and changes in vulnerability. We normalized disaster impacts, analyzed trends in the data and compared them with trends in extreme weather and climate events and vulnerability, following a 3 by 4 by 3 set-up, with three disaster burden categories, four regions and three extreme weather event categories. The trends in normalized disaster impacts show large differences between regions and weather event categories. Despite these variations, our overall conclusion is that the increasing exposure of people and economic assets is the major cause of increasing trends in disaster impacts. This holds for long-term trends in economic losses as well as the number of people affected. We also found similar, though more qualitative, results for the number of people killed; in all three cases, the role played by climate change cannot be excluded. Furthermore, we found that trends in historic vulnerability tend to be stable over time, despite adaptation measures taken by countries. Based on these findings, we derived disaster impact projections for the coming decades. We argue that projections beyond 2030 are too uncertain, not only due to unknown changes in vulnerability, but also due to increasing non-stationarities in normalization relations.